Variabilitas Klorofil-A Dan Suhu Permukaan Laut Berbasis Citra Satelit Himawari-8 Secara Spasial Dan Temporal Di Wilayah Perairan Utara Jawa Tengah - Sharina Sharina; Kusnandar Kusnandar; Heru K. Alamsyah (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2026)
The waters off the northern coast of Central Java are part of Fisheries Management Area (FMA) 712, which is characterized by high levels of fishing activity and complex oceanographic dynamics. Variations in Sea Surface Temperature (SST) and chlorophyll-a play a crucial role in determining primary productivity and potential fishing grounds. This current study seeks to investigate the spatial and temporal variability of SST and Chlorophyll-a, along with investigating the correlation between both parameters using Himawari-8 satellite imagery. The research method employed is quantitative descriptive, utilizing secondary satellite imagery data from the 2023–2025 period. Data analysis is conducted thru digital image processing, which includes the stages of pixel value extraction, data cleaning from cloud cover, and the calculation of monthly average values to represent seasonal changes. The Spearman rho correlation statistical test is applied to determine the strength and direction of the relationship between SPL and chlorophyll-a over time. The results indicate that SST and Chlorophyll-a at the study site fluctuate following seasonal patterns. Spatially, chlorophyll-a concentrations tend to be higher in coastal areas than in offshore areas. Correlation analysis indicates a strong negative conection between SST and chlorophyll-a, with a correlation coefficient of -0.713, suggesting that an increase in sea surface temperature is typically followed by a decrease in chlorophyll-a concentrations in the waters off northern Central Java